AKTIVITAS ANTIHIPERTENSI EKSTRAK ETANOL DAUN MATOA (Pometia pinnata J.R.Forst. & G.Forst.) PADA MODEL HEWAN HIPERTENSI YANG DIINDUKSI PREDNISON DAN NaCl - Kharina Septi Lestari; Elis Susilawati; Aulia Nurfazri Istiqomah; Silvi Nur Amalia; Widhya Aligita (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Hypertension is a disease without symptoms that is very dangerous (silent killer) because it is often not realized. Conditions that are not controlled and occur continuously will cause a disease factor related to cardiovascular disease. Empirically, matoa leaves are commonly used as antihypertensive drugs. This study aims to determine the activity of the ethanolic extract of matoa leaves as a diuretic and antihypertensive. Diuretic testing was carried out for 6 hours with urine volume measurement every hour. Each test animal was given warm water as a loading dose, using a comparison (Furosemide 3.6 mg/KgBW) and the matoa leaf ethanol extract test group with doses of 150, 300, and 500 mg/KgBW. Antihypertensive testing was carried out in a preventive manner using Prednisone 1.5 mg/KgBW and NaCl 2%, comparison (Hydrochlorothiazide 2.25 mg/KgBW) and the test group ethanol extract of matoa leaves with doses of 150, 300, and 500 mg/KgBW. given orally for 14 days. The test parameters were urine volume, systolic blood pressure and diastolic pressure. The data obtained were analyzed using One Way ANOVA and Kruskall Wallis. The results showed that the ethanol extract of matoa leaves could increase urine output, and decrease systolic and diastolic blood pressure because it had a comparable activity with the comparison group (p<0.05). A dose of 150 mg/kgBW has the most effective activity as an antihypertensive.